Assessment of fishery management parameters for major prey fish species in the lower reaches of the Songhua River - Lu, Wanqiao; Li, Peilun; Ma, Bo; Huo, Tangbin; Yin, Zengqiang; Tang, Fujiang; Wang, Jilong (Frontiers in Marine Science, 2023)
The stability of the ecosystem directly affects the water quality and safety, fishery production, and people’s quality of life along the route. In this study, extensive biological information on five dominant species of prey fish, including Hemiculter leucisculus (Basilewsky, 1855), Acheilognathus macropterus (Bleeker), Rhodeus sericeus (Pallas,1776), Pseudorasbora parva (Temminck & Schlegel, 1846), and Squalidus argentatus (Sauvage & Dabry de Thiersant, 1874), was collected in the lower reaches of the Songhua River, and the population parameters and variation rules of these fish were evaluated. The results showed that at present, the fish resources in the lower reaches of the Songhua River were in an overexploited state. Although the growth rate of prey fish was accelerating, their growth potential was decreasing. In addition to the homogeneous structure of the fish community, it was increasingly evident that a high proportion of small-sized fish were present in the fish community. In addition, the growth length coefficients of the five prey fish species were all greater than 0.2, indicating that the prey fish were growing at a faster rate, and the range of the growth performance indicators were 3.49 ~ 4.37. Our data also demonstrated that the exploitation rates of Hemiculter leucisculus and Squalidus argentatus were both greater than 0.5, and the exploitation rates of all species were higher than Emax except for Pseudorasbora parva. Finally, based on the above results, the mesh size of all nets should be controlled above 45 mm to ensure the size of the main prey fish populations in the lower reaches of the Songhua River. In summary, these results provided variation rules and growth of prey fish resources in the lower reaches of the Songhua River. At the same time, the distribution of major commercial or endangered baiting grounds in the lower reaches of the Songhua River was determined, which was beneficial to the balance and integrity of the ecosystem.